Quality of Women's Role in Social, Economic and Political Dimensions and the Role of Academic Institutions in Making It Happen - Safitra, Linda (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
In various dimensions of social life, especially in the social, economic and political dimensions, there are differences in the quality of roles between men and women, where the quality of women's roles in these three dimensions is still very weak. This cannot be separated from the social order and system that develops in society, such as labels given to women which indirectly hinder women's movements. The maximum role of academic institutions is also expected to improve the quality of women's roles. If we pay attention so far, it is very clear that the role of academic institutions has not been able to function optimally in improving the quality of women's roles. Therefore, this discussion wants to explain the quality of women's roles in social, economic and political aspects, as well as what steps academic institutions must take to make this happen.